Marketing minority language as a valid tool in the fight for survival of minority languages - Brezigar, Sara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The concept of marketing minority languages rests on the model that conceptualises minorities as communities formed by concentric circles of minority members. Every concentric circle corresponds to a group of minority members of different intensity, from those who represent the core of the linguistic minority, to those who merely speak a couple of words in the minority language. Marketing minority languages as an approach towards the preservation of minority languages presumes that it is possible to motivate inhabitants of a territory, where two linguistic communities live, to learn and use the minority language in their everyday life. Therefore, it assumes that linguistic minority members can and do move from one concentric circle to another, and that they can be motivated to come closer to the core of the linguistic minority. As such, marketing minority language can represent a valid tool in the fight for survival of minority languages, as well as a means against assimilation of the linguistic minority members. The article applies the concept of marketing minority languages to the Slovenian minority in Italy and explores new perspectives of development for the above mentioned community.
Keywords: Slovene; slovenščina; narodne manjšine; jezikovne manjšine; jezikovna politika; promocija; Promotion; raba jezika; Italija; Italy; zamejski Slovenci